Decolonizing the Body of Christ
XXVIII, 199 p.
Keywords: The first book in the new Postcolonialism and Religions series offers a preview of the series focus on multireligious, indigenous, and transnational scholarly voices. In this book, the once arch enemies of Religious studies and Postcolonial theory become critical companions in shared analysis of major postcolonial themes.